2015
DOI: 10.1155/2015/982679
|View full text |Cite
|
Sign up to set email alerts
|

Two Rare Cases of Hepatocellular Carcinoma after Kasai Procedure for Biliary Atresia: A Recommendation for Close Follow-Up

Abstract: The instigation of the Kasai procedure in infants who are born with biliary atresia has led to increased survival in this population for over half a century. The many complications that arise as a result of biliary atresia led to an early death for most patients. However, the Kasai procedure is not without its own impediments. Among them is the development of hepatocellular carcinoma. We present two cases of hepatocellular carcinoma, after Kasai procedure, from two different age groups, as a recommendation tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 14 publications
(19 reference statements)
0
9
0
Order By: Relevance
“…256 Biliary atresia may be predisposed to development of a malignancy albeit rare, even after the child has had a successful Kasai surgery as these children often develop cirrhosis. 257 Patients with progressive familial intrahepatic cholestasis (PFIC) type 2 present with pruritus and jaundice secondary to bile salt export pump deficiency and are at up to 10% risk for development of HCC by 2 years of age. 258 In cholestatic syndromes that may not be associated with cirrhosis like Alagille's, PFIC 1, and PFIC 3, there is low risk of development of a liver malignancy.…”
Section: Etiologymentioning
confidence: 99%
“…256 Biliary atresia may be predisposed to development of a malignancy albeit rare, even after the child has had a successful Kasai surgery as these children often develop cirrhosis. 257 Patients with progressive familial intrahepatic cholestasis (PFIC) type 2 present with pruritus and jaundice secondary to bile salt export pump deficiency and are at up to 10% risk for development of HCC by 2 years of age. 258 In cholestatic syndromes that may not be associated with cirrhosis like Alagille's, PFIC 1, and PFIC 3, there is low risk of development of a liver malignancy.…”
Section: Etiologymentioning
confidence: 99%
“…The discrepancy between imaging and histopathology in the setting of BA has been reported in 32 pediatric cases [ 2 , 3 , 10 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. The prevalence of HCC in explants of 544 children transplanted for BA was reported to be 1.2% [ 3 , 10 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Half of HCC seem to be missed during pre-LT imaging, and 41% of BA patients with HCC have a normal AFP [ 3 ]. The calculated sensitivity for the radiological diagnosis of HCC within the available literature of BA is 62.5% [ 2 , 3 , 10 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 29 , 30 , 31 , 32 , 33 ]. AFP was also of very limited use in our series, since it was only increased in one of the two patients with HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Okuyama et al [5] reported the cases of HCC occurrence after BA surgery in 1965, and thereafter a total of 25 cases have been reported from Japan and overseas [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21], of which 10 were from Japan [6-11, 18, 21].…”
Section: Discussionmentioning
confidence: 99%
“…And, MRI findings finally led to the diagnosis of HCC. Some reports recommend regular follow-up by MRI to ensure the accuracy and to avoid radiation exposure [13,14,16,20]. These facts led us to consider it necessary to accumulate more data on the selection of subject cases (states) and the frequency of performing MRI.…”
Section: Archives Of Clinical and Medical Case Reports 113mentioning
confidence: 99%